Análisis y diseño de una red FTTH para la CNT-EP en el sector Histórico de Chillogallo - Gutiérrez Largo, Vladimir Martín (2017)
The boom in internet services that support higher bandwidth has been greatly increased by the development of new electronic devices that allow access to online multimedia content, cloud storage, social networks and video on demand. This fact generated a greater demand for high access bandwidth Internet connections, Chillogallo's historic sector has an ADSL access network operated by CNT EP, which has on average a subscriber distance of 2.5km, limiting the increase of bandwidth for Users of the sector. Due to this, the design of a network that covers the subscribers of the sector with greater bandwidth than those provided by the current network. It proposes a Gigabit FTTH network (GPON) that uses the current network infrastructure and allows solving the problem of subscriber distances and the necessary bandwidth to meet current and future needs. The results of the design indicate an optical budget of 23.5dB with a calculation error compared to the simulation of 3.5% and economic indicators of net present value NAV in the order of $ 4261.7, internal rate of return IRR of 9.17% and recovery of initial investment of 11 months, determining the technical and financial feasibility of the project.